Equity markets and financial services in the Caribbean : some institutional imperatives - Jones-Hendrickson, Simon ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Presents a methodological analysis of the imperatives that are necessary to understand what it will take to interface equity markets and financial services in the commonwealth Caribbean such that the capital of these markets and services are made more widely available to a larger cross-section of the people.